Thermoelectric topping cycles with scalable design and temperature dependent material properties. (15th January 2016) - Yazawa, Kazuaki; Shakouri, Ali
Graphical abstract: System power output and incremental cost for a 540 MW scale coal-fired Rankine cycle power plant with a thermoelectric topping cycle (TP, ZT ∼ 0.7) or a thermoelectric waste heat recovery from flu gas (WHR, ZT ∼ 1.0) as functions of average ZT of thermoelectric materials. Abstract: Analysis and optimization of topping thermoelectric generators with bottoming Rankine cycle is presented. Interface temperature between the two cycles is optimized for fuel efficiency. It is shown that the topping thermoelectric generator may increase the system efficiency by 6% for a coal-fired power plant with approximately 0.2–0.3 /W in material cost. The topping cycle can be a viable large scale application of thermoelectric generators since peak ZT of the material can be optimized in a narrow temperature range without cascading.